Performance of IFAT, ELISA, direct parasitological examination and PCR on lymph node aspirates for canine visceral leishmaniasis diagnosis - Camargo, J. B. [UNESP]; Langoni, Hélio [UNESP]; Troncarelli, M. Z. [UNESP]; Machado, J. G. [UNESP]; Lucheis, Simone Baldini [UNESP]; Padovani, C. R. [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2010)
Canine visceral leishmaniasis (CVL) is endemic in numerous Brazilian regions. The greatest difficulty in controlling the disease is the diagnostic limitation. In the present study, the most common tests employed for visceral leishmaniasis diagnosis were compared: immunofluorescence antibody test (IFAT), immunoenzymatic assay (ELISA), direct parasitological examination and polymerase chain reaction (PCR). Samples of lymph node aspirates and blood were collected from 100 dogs that lived in an endemic area (Bauru city, São Paulo state) and from 100 negative controls from a non-endemic area (Botucatu city, São Paulo state). Specificity of both IFAT and PCR was 100% whereas ELISA was 99%. Sensitivities were 97.77, 93.33 and 91.11% respectively for IFAT, ELISA and PCR.
Keywords: visceral leishmaniasis; dog; diagnosis